Teologi Inkarnasi dan Gereja Yang Inkarnatoris menurut Hans Urs von Balthasar - Anton Dewa (Sekolah Tinggi Filsafat Seminari Pineleng, 2021)
The uniqueness of Balthasar's theology of incarnation lies in the fact that he bases his arguments of kenosis primarily on the Bible and the theology of patristics. On this basis, he confronts the systematic theological exposition of incarnation with the question of God in modern times. Balthasar represents the centre of his theological principle in the